Inovasi Eco-Green Bottle Press sebagai Solusi Teknologi Tepat Guna dalam Reduksi Volume Sampah Plastik Berbasis Pemberdayaan Masyarakat - Amanda Nur Fajriah; Jumiarty Elsabilla; Syabilla Nuraini; Gina Sri Rahmawati; Ahmad Yoga (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The management of plastic waste, particularly Polyethylene Terephthalate (PET) derived from used beverage bottles, poses a critical challenge in rural areas due to its bulky nature. This condition directly contributes to low logistical efficiency in waste transportation and sorting activities at community waste banks. This study aims to design, manufacture, and test the effectiveness of the Eco-Green Bottle Press as an appropriate technology (AT) solution to reduce the volume of plastic bottle waste directly at the source. The research employed a Research and Development (R&D) approach integrated with a Descriptive-Applicative method, implemented through a socialization program and field trials. The device operates using a second-class lever mechanical system to multiply manual pressing force instantaneously without the use of electrical energy. Real-world implementation was conducted in Pasir Tanjung Village, Cikarang Pusat District, Bekasi Regency, involving community representatives from diverse physical backgrounds and age groups. Testing results demonstrated that the device is capable of reducing the dimensional volume of 600 ml plastic bottles by 70%–80%. Ergonomic and operability assessments confirmed that the device is highly safe, stable, and lightweight for independent use by housewives and adolescents alike. With a remarkably economical production cost ranging from IDR 150,000 to IDR 200,000 utilizing locally sourced material components, this innovation is feasible for mass replication to strengthen the circular economy value chain of rural waste banks.